x-y=-3

Subtract x from both sides of the equation.

-y=-3-x

Multiply each term in -y=-3-x by -1

Multiply each term in -y=-3-x by -1.

(-y)⋅-1=(-3)⋅-1+(-x)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=(-3)⋅-1+(-x)⋅-1

Multiply y by 1.

y=(-3)⋅-1+(-x)⋅-1

y=(-3)⋅-1+(-x)⋅-1

Simplify each term.

Multiply -3 by -1.

y=3+(-x)⋅-1

Multiply (-x)⋅-1.

Multiply -1 by -1.

y=3+1x

Multiply x by 1.

y=3+x

y=3+x

y=3+x

y=3+x

y=3+x

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Reorder 3 and x.

y=x+3

y=x+3

Find the values of m and b using the form y=mx+b.

m=1

b=3

The slope of the line is the value of m, and the y-intercept is the value of b.

Slope: 1

y-intercept: 3

Slope: 1

y-intercept: 3

Choose 0 to substitute in for x to find the ordered pair.

Replace the variable x with 0 in the expression.

f(0)=(0)+3

Simplify the result.

Add 0 and 3.

f(0)=3

The final answer is 3.

3

3

The y value at x=0 is 3.

y=3

y=3

Choose 1 to substitute in for x to find the ordered pair.

Replace the variable x with 1 in the expression.

f(1)=(1)+3

Simplify the result.

Add 1 and 3.

f(1)=4

The final answer is 4.

4

4

The y value at x=1 is 4.

y=4

y=4

Create a table of the x and y values.

xy0314

xy0314

Graph the line using the slope and the y-intercept, or the points.

Slope: 1

y-intercept: 3

xy0314

Graph x-y=-3